Resource sharing today a practical guide to interlibrary loan, consortial circulation, and global cooperation - Nyquist, Corinne (Lanham, Maryland Rowman & Littlefield, 2014)
"Budget constraints challenge collection development in unprecedented ways. Collection development has increasingly become a cooperative effort among libraries in geographic proximity. When their own library doesn't have certain books or journals, users turn to interlibrary loan to obtain the resources they need. However, many library science degree programs don't cover interlibrary loan. Resource Sharing Today is a practical guide to resource sharing starting with the library across town and ending with libraries on the other side of the globe. Chapters cover everything from the ALA's interlibrary loan form to successful innovations such as Virginia Tech's ILLiad to New York's IDS (Information Delivery Service). Appendices include regional, state, national, and international ILL codes, ALA and IFLA forms, open access agreements, and purchase on demand plans." -- Publisher's description.
Teaching one another ILL since the library schools don't do it -- MARC : Library of Congress did it and changed it, and it affects ILL -- OCLC : how to get them to listen to us -- Innovation can come from us : ILLIad is one example -- Rethinking library resource sharing : the future of interlibrary loans -- Don't just say "no" when faced with rules and policies -- Showing users what they missed in the library : ILL as reference -- Buy or borrow? : getting what the patron needs -- Conundrums : confusing and difficult problem or question -- Going global : it's easier than you think -- On-the-spot interlibrary loan -- Enhancing discovery : taking responsibility at the local level -- Appendix A. Code of ethics of the American Library Association -- Appendix B. Interlibrary loan code for the United States -- Appendix C. Interlibrary loan code for the United States explanatory supplement -- Appendix D. ALA and ARL response to the Section 108 Study Group Regarding Interlibrary Loan and Other Copies for Users -- Appendix E. Interlibrary loans : ALA library fact sheet number 8 -- Appendix F. Five things every new resource-sharing librarian should know -- Appendix G. About IFLA -- Appendix H. IFLA guidelines for best practice in interlibrary loan and document delivery -- Appendix I. Libraries Very Interested in Sharing (LVIS) fact sheet, Illinois State Library.
Includes bibliographical references and index.
Keywords: Library cooperation; Library cooperation -- United States; Interlibrary loans; Interlibrary loans -- United States; Document delivery; Document delivery -- United States; Cooperative collection development (Libraries); Cooperative collection development (Libraries) -- United States